mRNA therapy: A new frontier in regenerative medicine - Ding‐Ding Xue; Yue Zhang; An‐Ran Shen; Tao‐Tao Tang; Bi‐Cheng Liu; Lin‐Li Lv (Interdisciplinary Medicine)
Abstract Tissue regeneration has raised intensive attention due to its great significance in overcoming various diseases resulting from different injuries. Since the COVID‐19 pandemic, mRNA therapeutics have emerged as innovative strategies in the prevention and treatment of diseases due to their unique advantages. Compared to traditional regenerative strategies, mRNA therapy offers rapid translation into proteins with low production cost and high modifiability. Herein, we discuss the progress in the key processes of mRNA therapy, focusing on therapeutic mRNA modification and delivery carriers. The preclinical and clinical studies of mRNA therapeutics for regeneration of cardiac, lung, liver, kidney, locomotor system, skin lesions and neurological disorders were summarized comprehensively. Developing strategies to reduce immunogenicity and off‐target effects, as well as optimization of the delivery system may accelerate the pace of clinical translation.